Robert Mugabe’s 1980 candidature as depicted in the (South African) Sunday Times - Johann C de Wet (Communicare)
Zimbabwean President Robert Mugabe has now been in power for three decades. He has acquired an almost universal image of being a dictator who has steadily governed the country to ruin. This article investigates the depiction of Robert Mugabe’s candidature in the 1980 Zimbabwean (common roll) independence election campaign in the Sunday Times, then by far the largest South African newspaper. A content analysis of the coverage is followed by argumentation that brings the content of the coverage in line with the general culture of the newspaper. The Sunday Times employed mainly stereotypical images of Mugabe. For it, the Zimbabwean independence election campaign revolved respectively around a choice for Southern Africa between capitalism and Marxism and between the future of white and black power. Mugabe was depicted as an enemy both of capitalism and of continued white interests